A quantitative and qualitative thermal comfort assessment in urban public squares of the inhabitants of desert regions - Guedouh, Marouane Samir; Khadraoui, Mohamed Amine (Technium Social Sciences Journal, 2022)
This article examines the indicators of residents' needs for thermal comfort in public spaces. Our hypothesis focuses on the extent to which high temperatures are associated with the use of public spaces by different age groups of the population. The public squares that distinguish the urban areas of the case study were selected based on their importance and location in the city center. The research methodology is based on numerous research techniques: in situ measurements, observation schemes and questionnaires. The most important results obtained for a better design of the public square must be adapted to the needs of the user taking into account essential elements such as the quality of the equipment of the place, the type and density of the vegetation, the inclusion of water bodies and the perception of the inhabitants...etc, in addition to giving importance and highlighting the social and cultural aspects and the identity of the region.